One Village One Dam project to benefit from fisheries production - Mapedza, Everisto D. (GH Environment, 2023)
Press item on One of the government’s flagship programmes called One Village One Dam (1V1D) in Ghana which is set to benefit from fisheries production through the help of the Resilient Aquatic Food Systems initiative.